MIXED CODE THAT ENTERENCHED IN THE LEARNING PROCESS BY CHATHOLIC JUNIOR HIGH SCHOOL GONZAGA TOMOHON - Mayske Rinny Liando; Tirsa Vira Rondonuwu (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2019)
The teaching of second language or the third make sociolinguistic problem. For most Indonesian people, Indonesian language is the second or third language. The teaching of of Indonesian language is integrated in Indonesian language subject that starts from elementary to high school. Indonesian language is a main language in Indonesian especially in education institutes. It is undebieble fact that students use another language at Gonzaga Junior High School Tomohon because of the influence of social and culture background. Code mixing is caused by some factors, namely (1) subject, (2) describing, (3) daily routine in teaching and learning activities in Junior High School Catholic Gonzaga Tomohon has been the main issue in their research.This research is aimed to explain about kinds of code mixing and factors that cause the code mixing in teaching and learning activities by Junior High School Students Catholic Gonzaga Tomohon.Theories used for this research is the theory of speech community, bilingual theory , theory of code and code mixing. This research is a descriptive qualitative. The research data is done with the following method of observation technic. The data in this research is the student speech that contains code mixing. The data analysis that use is qualitative analysis with equal method.The result of this research shows that speech act of the students in Gonzaga Junior High School of Tomohon found code mixing. The form of code mixing that using are Indonesian, English and Manado Malay. Based on the result of this research can concluding that kinds of code mixing are code mixing in lexical form, frasa form and clausa form. The factors of code mixing are namely, describing and daily routine. Key words: code mixing, teaching and learning activities, Indonesian language, sociolinguistic